Soluble plasma-derived von Willebrand factor assembles to a haemostatically active filamentous network - Barg, Alexej; Ossig, Rainer; Goerge, Tobias; Schneider, Matthias F.; Schillers, Hermann; Oberleithner, Hans; Schneider, Stefan W. (Thrombosis and Haemostasis, 2007)
The large glycoprotein vonWillebrand factor (VWF) is involved in the initial haemostatic reaction mediating the interaction between platelets and the injured vessel wall. It has been demonstrated that unusually large VWF (ULVWF) multimers after being released from endothelium are capable of developing elongated membrane-anchored strings that are hyperactive to bind platelets. In the present study we investigated whether soluble plasma-derived VWF is competent to develop similar thrombotically active multimers. We demonstrated that soluble VWF multimers isolated from human plasma self-assemble to a network of fibers immobilized on a collagen matrix and are functionally active to bind platelets. Formation of these VWF fibers depends on shear flow, concentration of solubleVWF, and a suitable binding surface. Self-assembly of soluble VWF does not require the presence of cellular membrane ligands. The network of fibers is subjected to rapid degradation by proteolytic activity of plasma ADAMTS-13.Atomic force microscopy images elucidate the nanostructure of VWF fibers and illustrate self-association and -aggregation of several filamentous multimers. Together, these results suggest that circulatingVWF can contribute to a formation of hyperactive VWF fibers on exposed subendothelial collagen during vascular injury.
Keywords: ULVWF multimers; platelet adhesion; atomic force microscopy; soluble VWF